Performance and characteristics of dynamic membranes for dairy wastewater treatment under anaerobic conditions - SEMERCİ, NESLİHAN (My University, 2023)
© 2023, The Author(s) under exclusive licence to Iranian Society of Environmentalists (IRSEN) and Science and Research Branch, Islamic Azad University.The aim of this study was to treat dairy wastewater by using an anaerobic dynamic membrane bioreactor equipped with a 20-µm polyester mesh filter and at organic loading rate of 8.1 ± 1.5 kg COD/(m3 day). The dynamic membrane was formed in 42 d, and the operation was continued for additional 50 days. In order to prevent membrane fouling and to ensure efficient cake layer formation, a wide range of cross flow velocity ranging from 5 m/h to 54 m/h was applied until a stable cake layer was formed. The chemical oxygen demand removal efficiency was 85 ± 9% in the dynamic membrane formation period (Day 0–42). In the stable operational period, the chemical oxygen demand removal improved by more than 10% owing to the well-developed Dynamic Membrane. Carbon, calcium, phosphorus, oxygen, and sulfur elements were detected in selected points of the dynamic membrane layer. Proteins and polysaccharides were detected in the dynamic membrane layer as organic compounds. The inorganic compounds in dynamic membrane layer were detected and found as 1.16% sodium, 1.50% magnesium, 0.76% potassium, 3.34% calcium, and 0.41% iron in mass concentration. The analysis results showed that organic and inorganic materials led to the formation of a strict/dense cake layer.
Keywords: Tarımsal Bilimler; Ziraat; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Tarım Bilimleri; Mühendislik; MÜHENDİSLİK, ÇEVRE; ZİRAAT MÜHENDİSLİĞİ; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); AGRICULTURAL SCIENCES; ENGINEERING; ENGINEERING, ENVIRONMENTAL; AGRICULTURAL ENGINEERING; Çevre Mühendisliği; Fizik Bilimleri; Çevre Kimyası; Genel Tarım ve Biyoloji Bilimleri; Yaşam Bilimleri; Environmental Engineering; Physical Sciences; Environmental Chemistry; General Agricultural and Biological Sciences; Life Sciences; Anaerobic membrane bioreactor; Dynamic membrane components; Membrane filtration; Polyester mesh